ʺStorytelling as a way to remember everything - psychological and pedagogical training of future teachers and engineer-teachersʺ - Lytvyn , S. (Problems of Engineer-Pedagogical Education, 2024)
The article analyzes the principles and features of the introduction of storytelling technologies into the educational process as a pedagogical technique based on the use of stories with a certain structure and hero, aimed at solving pedagogical problems of learning, mentoring, development and motivation. Currently, education is facing serious problems, such as information overload, inefficient use of modern teaching methods and technologies, communication breakdowns between teachers, students and stakeholders, separation of theoretical knowledge acquired in higher education institutions from practice. A system of new pedagogical techniques (tools), one of which is storytelling, is designed to solve these problems. Initially, storytelling proved itself as a fairly effective means of building external and internal corporate communications, that is, in the field of personnel management and management. Now it is actively used in business, PR, marketing and journalism. The purpose of this article is to show the possibility of using storytelling in the pedagogical field (in online and offline formats), highlight its features, recommend the main plots for their inclusion in the teaching methodology of disciplines in higher education before creating educational tasks, transfer of explicit and implicit knowledge. The article defines the main components of pedagogical storytelling, the rules and principles of introducing storytelling technologies into the educational process. The criteria for the effectiveness of storytelling have been determined and analyzed. The concept of didactic potential of storytelling technology is defined. The article examines the possibility of using pedagogical storytelling as a modern technique of constructing educational tasks in the disciplines of psychological and pedagogical training of students of pedagogical and engineering pedagogical specialties. Proposed, described and analyzed plot-constructors and structural components of creating pedagogical storytelling, examples of their application are given This teaching technique is recommended to be used to motivate students, explain a process or phenomenon, choose means of solving problems, model problem situations, and explain the course of action.